An LMI Approach to Hâ Performance Analysis of Continuous-Time Systems with Two Additive TimeVarying Delays - Ridwan, Wrastawa; Trilaksono, Bambang Riyanto (ITB Journal Publisher, LPPM ITB, 2011)
ThisÂ paperÂ investigatesÂ theÂ problemÂ ofÂ Hâ performanceÂ analysisÂ for continousâtime systems with two additive time -varying delays in the state.Â Our objective is focused onÂ stabilityÂ analysis ofÂ aÂ continuousÂ system with two timevaryingÂ delaysÂ withÂ anÂ Hâ disturbanceÂ attenuationÂ levelÂ Î³.Â ByÂ exploiting Â Lyapunov-Krasovski functional and introducing free weighting matrix variables, LMI stability condition have been derived.